A strategy to help trees suffering from drought. Issue 4 (2nd August 2021) - Mattheck, Claus; Fink, Siegfried; Bethge, Klaus; Weber, Karlheinz; Tesari, Iwiza
ABSTRACT: Due to long and dry summers dead trees are a problem which is almost global in its occurrence. Here, based on field studies, a simple remedy is proposed that addresses the issues. This remedy is for trees already planted and includes a modification of the planting process. The key idea is a vertical borehole to be filled with a mix of gravel and biochar (Terra preta). These gravel poles in the ground are resistant to compaction by traffic-related vibrations. Furthermore, air, water and nutrients in the gravel-biochar mix serve to attract root growth. This approach draws the roots into deeper, moister soil layers where water can be taken up and thus they serve to enhance tree survival.